Application of an innovative technique for unilateral ovariectomy in dairy cows. (5th November 2016) - Rizzo, A.; Piccinno, M.; Lacitignola, L.; D'Onghia, G.; D'Onghia, G. F.; Sciorsci, R. L.
Abstract : This report describes an innovative unilateral ovariectomy technique for the surgical treatment of follicular cysts in dairy cows. Five cows, with a diagnosis of follicular cysts, were submitted to unilateral ovariectomy via a paralumbar fossa approach, in standing position. The linear cutter proved useful for clamping the ovary, stapling the vessels and cutting in one stroke, thus reducing surgery times. After unilateral ovariectomy, all cows underwent heat 7–30 days after surgery, and three cows became pregnant. All cows showed increased milk production. The results of this case report showed that flank ovariectomy, performed in this way, is an efficient, low‐risk technique for surgical treatment of follicular cysts in dairy cows.